2021
DOI: 10.3390/molecules26061534
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation and Noncovalent Functionalization of Graphene Surface with Poly-N-Vinyl-2-Pyrrolidone by In Situ Polymerization

Abstract: Heteroatom functionalization on a graphene surface can endow the physical and structural properties of graphene. Here, a one-step in situ polymerization method was used for the noncovalent functionalization of a graphene surface with poly-N-vinyl-2-pyrrolidone (PNVP) and the exfoliation of graphite into graphene sheets. The obtained graphene/poly-N-vinyl pyrrolidone (GPNVP) composite was thoroughly characterized. The surface morphology of GPNVP was observed using field emission scanning electron microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…DCM was found to be a good solvent to disperse graphene using PVK-b-PVP polymer [ 120 ]. Graphite was partially exfoliated and dispersed in water by in situ polymerization on the graphene surface [ 121 ].…”
Section: Stable Graphene Dispersions Using Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…DCM was found to be a good solvent to disperse graphene using PVK-b-PVP polymer [ 120 ]. Graphite was partially exfoliated and dispersed in water by in situ polymerization on the graphene surface [ 121 ].…”
Section: Stable Graphene Dispersions Using Polymersmentioning
confidence: 99%
“…( a – f ) images reproduced from ref. [ 121 ]. AFM topographic images and corresponding height profiles of graphene–polyvinyl pyridine (11 k and 27 k): ( g – i ) ethanolic graphene dispersions and ( j – l ) aqueous graphene dispersions.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Block copolymers have shown better performance in this regard. Recently, Perumal et al produced stable dispersions of graphene in ethanol, isopropanol, and methanol by employing polypyridine-, polystyrene-, and poly-N-vinyl-2-pyrrolidone-based block copolymers [17][18][19][20]. Qamar et al reported a non-ionic block copolymer (Lugalvan BNO12) for dispersing graphene in aqueous solutions [21].…”
Section: Introductionmentioning
confidence: 99%